Aorto Femoral Bypass Graft in Chronic Limb Ischemia Patient - R. Muhammad Budiarto, MD; M. Rifqi D. Hasan (Universitas Airlangga, 2021)
A 44-year-old man was admitted to hospital to be performed re-thrombectomy after previously performed thrombectomy at the referring hospital but did not show clinical improvement. CT angiography results before re-thrombectomy showed a central thrombus measuring 1.1 cm in diameter, and an impression of 2.6 cm long at the branching of the right external Iliaca artery which caused total obstruction of the right illiaca external artery to the distal. Aortofemoral bypass graft surgery is a procedure utilized commonly for the treatment of aortoiliac occlusive disease. The treatment given to manage symptoms if medical management or minimally invasive therapy, such as balloon angioplasty and stenting, was unsuccessful or unsuitable for the patient. Aortofemoral bypass graft surgical procedure was performed on the patient. However, post procedure angiography showed no visible flow through the newly placed graft. A repair graft procedure was planned for the patient, but the patient refused to undergo further surgical procedures.